Geography and international conflict : Ukraine, Taiwan, Indo-Pacific, and Sino-American relations - Chan, Steve; Hu, Weixing (Researcher on world politics) (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book analyses the influence of geography-defined broadly to refer to physical size, location, terrain, accessibility, insularity, climate, regions, neighborhoods, natural endowment, strategic pathways, maritime and continental orientations, and even imagined communities-on international relations. Drawing on evidence and insights from cross-national research the book highlights geography's enduring importance in and relevance to the ongoing Russo-Ukrainian War, tension across the Taiwan Strait, construction of reginal order such as Greater Eurasia and Indo-Pacific, and important differences in the nature of the security environment facing China and the United States respectively. It successfully bridges the gap that often separates international relations scholarship, interested in the central tendencies characterizing how states interact in general, and more idiographic approaches of Sinology, providing rich country-specific details, but at the expense of often overlooking features that China shares with other countries. Offering an overview of propositions about how geography has shaped human development and institutions, alongside in-depth discussions of its role in influencing national security and interstate conflict, this book will appeal to students and scholars of international relations, political geography and comparative politics"--
Introduction : geopolitics' revival and our plan for the book -- The long arc of geographic influence -- Geography's influence on international relations -- Mackinder, Spykman, and Mahan : is geopolitics still relevant today? -- Ukraine : key to the Eurasian heartland? -- Taiwan : lock on China's front door -- Why the Indo-Pacific? : regionalism and imagined communities -- Comparing China and the United States' security environment -- Conclusion : managing international relations in a hybrid world of new and old.
Keywords: Geopolitics; Geopolitics -- Case studies; World politics -- 1989-; Geopolitics -- Ukraine; Geopolitics -- Taiwan; Geopolitics -- Indo-Pacific Region; Geopolitics -- China; Geopolitics -- United States; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Government / Comparative